2023
DOI: 10.1097/shk.0000000000002065
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Models for Predicting Acute Kidney Injury in Patients With Sepsis-Associated Acute Respiratory Distress Syndrome

Abstract: Background: Acute kidney injury (AKI) is a prevalent and serious complication among patients with sepsis-associated acute respiratory distress syndrome (ARDS). Prompt and accurate prediction of AKI has an important role in timely intervention, ultimately improving the patients' survival rate. This study aimed to establish machine learning models to predict AKI via thorough analysis of data derived from electronic medical records. Method: The data of eligible patients were retrospectively collected from the Med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…At present, multiple machine learning techniques are being employed in critical care studies. Specific applications include early detection of acute kidney injury, pulmonary embolism, gene expression in sepsis, and leukocyte phenotyping when trying to understand the pathophysiology of sepsis (45)(46)(47)(48)(49). Reinforcement learning has also been used to formulate ICU electrolyte replacement protocols and determine treatment decisions in sepsis (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…At present, multiple machine learning techniques are being employed in critical care studies. Specific applications include early detection of acute kidney injury, pulmonary embolism, gene expression in sepsis, and leukocyte phenotyping when trying to understand the pathophysiology of sepsis (45)(46)(47)(48)(49). Reinforcement learning has also been used to formulate ICU electrolyte replacement protocols and determine treatment decisions in sepsis (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that ML has good predictive value for in-hospital mortality rate in ARDS patients caused by trauma. In addition, a study constructed a prognostic model for sepsis-induced ARDS patients using ML to predict the occurrence of AKI within 48 hours of admission to the ICU, achieving a high AUC of 0.86 and accuracy of 0.81 [23]. Moreover, several other studies have demonstrated the ability of ML to predict the duration of mechanical ventilation in ARDS, indicating that it can provide early and accurate predictions for MV duration in ARDS [13,24].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been a growing interest in utilizing machine learning (ML) algorithms for diagnostic and prognostic disease studies. These ML models have shown to surpass traditional scoring methods in terms of predictive accuracy ( 15 , 16 ). In our study, we also observed that machine learning models outperformed conventional scoring systems in all 28-day mortality prediction for S-AKI patients.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al utilized data from the MIMIC III database to create a machine learning model for predicting AKI within 48 h of sepsis-related ARDS cases. Their model outperformed the discriminatory ability of SOFA ( 16 ). This highlights the potential of machine learning algorithms in accurately predicting the development of S-AKI.…”
Section: Introductionmentioning
confidence: 98%